2016
DOI: 10.1111/pai.12528
|View full text |Cite
|
Sign up to set email alerts
|

Patient quality of life following induction of oral immunotherapy for food allergy

Abstract: Pre-OIT reaction severity affects quality of life in both preschool and school-aged food-allergic children. In contrast, a lower maximal tolerated dose during OIT induction is associated with worse indices of quality of life primarily in children aged 6-12 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 29 publications
5
45
0
Order By: Relevance
“…Oral immunotherapy is a promising therapy for FA. Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Oral immunotherapy is a promising therapy for FA. Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Discordances have been found in a study examining changes in QoL of children with FA during the updosing phase of OIT with improvement in 35%‐50% of patients, but deterioration in 25%‐30% . Certainly, a lower maximal tolerated dose during OIT induction is associated with worse indices of QoL primarily in children . Consequently, if the outcome of OFC or desensitization protocol does not change children's diet, and the fear for accidental exposure does not drive the need for accurate diagnosis, and then part of the beneficial effect of the food reintroduction might be lacking…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In this study, Epstein Rigbi et al. investigated the factors affecting quality of life in patients during the first week of OIT for food allergy. For this purpose, the Food Allergy Quality of Life Questionnaire for parents of children aged 0–12 years was translated into Hebrew and validated.…”
Section: Patients Quality Of Life Following Induction Of Oral Immunotmentioning
confidence: 99%